Lie Theory and Geometry 1994
DOI: 10.1007/978-1-4612-0261-5_8
|View full text |Cite
|
Sign up to set email alerts
|

Closedness of Star Products and Cohomologies

Abstract: We first review the introduction of star products in connection with deformations of Poisson brackets and the various cohomologies that are related to them. Then we concentrate on what we have called "closed star products" and their relations with cyclic cohomology and index theorems. Finally we shall explain how quantum groups, especially in their recent topological form, are in essence examples of star products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…For completeness we give here a brief review on deformation quantization and star-products; a full treatment can be found in [2], [3] and a recent review in [10]. Let M be a Poisson manifold.…”
Section: Deformation Quantizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For completeness we give here a brief review on deformation quantization and star-products; a full treatment can be found in [2], [3] and a recent review in [10]. Let M be a Poisson manifold.…”
Section: Deformation Quantizationmentioning
confidence: 99%
“…Our construction can be generalized to any orbit of the coadjoint action of a Lie algebra on its dual (the case of R 3 corresponds to su(2) ⋆ ). In that case, instead of the Moyal product appearing in the evaluation map, one can use a covariant star-product on the orbit [10].…”
Section: Zariski Productmentioning
confidence: 99%